2016
DOI: 10.1038/pr.2016.185
|View full text |Cite|
|
Sign up to set email alerts
|

Medical morbidities and DNA methylation of NR3C1 in preterm infants

Abstract: Background:Although there are no accepted “normal” levels of circulating cortisol in preterm infants, critically ill preterm infants show lower cortisol levels than healthy preterm infants. The regulation of cortisol reactivity by epigenetic changes in glucocorticoid receptor gene (NR3C1) expression has been demonstrated. This study aims to examine the relationship between medical morbidities in preterm infants and DNA methylation of NR3C1.Methods:Pyrosequencing was used to determine DNA methylation in CpG sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 39 publications
0
20
0
Order By: Relevance
“…Specifically, increased methylation of glucocorticoid receptor gene was observed in the first 4 days following preterm birth. However, findings remain inconsistent as studies demonstrated both decreased and increased DNA methylation of NR3C1 in high-risk preterm infants [i.e., scoring high on Neonatal Intensive Care Unit Network Neurobehavioral Scale (NNNS) or more medical problems] compared to low-risk preterm infants ( 200 , 201 ).…”
Section: Mechanisms Underlying Later Life Resilience and Vulnerabilitmentioning
confidence: 99%
“…Specifically, increased methylation of glucocorticoid receptor gene was observed in the first 4 days following preterm birth. However, findings remain inconsistent as studies demonstrated both decreased and increased DNA methylation of NR3C1 in high-risk preterm infants [i.e., scoring high on Neonatal Intensive Care Unit Network Neurobehavioral Scale (NNNS) or more medical problems] compared to low-risk preterm infants ( 200 , 201 ).…”
Section: Mechanisms Underlying Later Life Resilience and Vulnerabilitmentioning
confidence: 99%
“…Several platforms for detecting aberrantly methylated DNA are available, such as Illumina HumanMethylation 450 BeadChip array, DREAMing, and Illumina HumanMethylation27 Bead-Chip [ 59 , 60 , 61 , 62 , 63 , 64 , 65 ], but only NGS reports accurate information regarding the methylation status of each cytosine of the DNA loci. In order to reveal the simultaneous methylation of two cytosines in one DNA loci in clinical diagnostics, next-generation MPS combined with target enrichment protocols [ 66 ] can be employed, as well as mass-spectrometry-based platforms, such as MassARRAY from Agena Bioscience Inc. Actually, the last platform allows the fast and cost-efficient visualization of cytosines in given positions and can be modified to perform simultaneous cytosine localizations.…”
Section: Discussionmentioning
confidence: 99%
“…Although tissue specificity of NR3C1 DNAm likely exists, both placental tissue and our target tissue, buccal epithelial cells (or saliva), may represent key developmental phenotypes and have utility as biomarkers (Armstrong et al, 2014). In a recent study of infant buccal epithelial cells, preterm infants with more medical morbidities had lower NR3C1 DNAm, and the authors speculated DNAm as potentially promoting adaptive programming (Giarraputo et al, 2017). Further, in a study of mothers with posttraumatic stress disorder (PTSD), lower NR3C1 DNAm in saliva was associated with greater symptom severity and parenting stress; the authors posited that NR3C1 DNAm effect direction could be dependent on how exposures are individually “processed,” reflecting the importance of context (Schechter et al, 2015).…”
Section: Discussionmentioning
confidence: 99%